(untitled) - Kozai, T. (Chiba, Japan, 2002)
Photoautotrophic shoot and root development for triploid melon. Control of microbial contamination for large scale photauototrophic micropropagation.
Keywords: Plant propagation,Transplant production,Agriculture,Nhân giống cây trồng,Nhân giống cây trồng; environmental aspects